Who can become German? Xenophobia and attitudes towards naturalization - Claudia Diehl; Ingrid Tucci (DIW Economic Bulletin, 2011)
Germans are opening up to the topic of immigration: According to the representative data of this report, less and less Germans without a migration background feel threatened by immigration. Also, their attitude towards naturalization has changed. The question What is the decisive factor for granting German nationality? is now answered differently than in the 1990s. A significant part of the population without migration background considers ethnic German descent as less important. More and more Germans, however, believe that individual behavior should be the decisive factor for naturalization. In contrast, this doesn't necessarily imply a decline of xenophobia: Persons placing high importance on behavior and cultural adaptation have equally frequent xenophobic tendencies as persons considering ethnicity to be more important. Still, the number of Germans feeling strong hostility towards strangers went down.
Keywords: D01; D79; Z0; 330; immigration; xenophobia; naturalization